Corrosion Behaviour of a SiOxNy Coated and Nitrided PH Stainless Steel. (2015) - Dalibon, Eugenia L.; Moscatelli, Mauro; Simison, Silvia; Escalada, Lisandro; Cabo, Amado; Lasorsa, Carlos; Brühl, Sonia P.
Abstract: Precipitation hardening stainless steels are used in applications where wear and corrosion resistance are required. To improve the surface properties, thermochemical treatments in combination with hard coatings can be used. In this work, the corrosion behaviour of SiOxNy coatings deposited on nitrided and non-nitrided Corrax® PH stainless steel were evaluated comparing them with the behaviour of samples which were only nitrided (two different conditions of nitrogen percentage in the working gases were used). The microstructure was analyzed. Corrosion behaviour was evaluated by the Salt Spray Fog Test and cyclic potentiodynamic polarization in NaCl solution. Erosion-corrosion tests were conducted. The thickness of the coating was about 1.4 microns, and its hardness was 2300 HV. The film had better erosion and corrosion behaviour when it was deposited on the nitrided steel. This fact demonstrated that the nitrided layer results in a good interface that improves the adhesion and mechanical support.